Odpowiedzi

2010-04-10T21:47:30+02:00
4(2x+3)-2(4y-1)=30

5x+1 y -3
------ - ------- = 3
3 4


8x+3-8y=30

5x+1 y -3
------ - ------- = 3
3 4



8x-8y= -3+30

5x+1 y -3
------ - ------- = 3
3 4


8x-8y=27

5x+1 y -3
------ - ------- = 3
3 4



8x-8y=27

5x-y =-1+3+3 / 12


8x-8y=27
5x-y=5/12


8x-y=27
5x-y=0,41
2010-04-10T21:54:51+02:00
4(2x+3)-2(4y-1)=30
(5x+1)/3 - (y-3)/4=3 /*12

8x+12-8y+2 = 30 /-12
4(5x+1)-3(y-3) = 36

8x-8y = 18 /:8
20x+4-3y+9 = 36

x-y = 18/8
20x-3y = 23

x = 18/8+y
20x-3y = 23

20(18/8+y)-3y = 23
x = 18/8+y

45+20y-3y = 23
x = 18/8+y

17y = -22
x = 18/8+y

y = -1 i 5/17
x = 18/8+ 22/17

y = -1 i 5/17
x = 130/136 = 65/68